1985
DOI: 10.3354/meps025083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sediment copper on benthic fauna

Abstract: Relations between species diversity in benthic-fauna communities and sediment concentration of heavy metals (Cu, Pb, Zn) and organic matter were tested by correlation and regression analyses on data from Norwegian fjords. Diversity and Cu showed a strong negative correlation. A moderate negative correlation was found for Pb and a weak negative correlation for Zn. Diversity and organic matter showed a moderate negative correlation. The negative correlation between diversity and Cu is interpreted as a cause-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 15 publications
6
55
1
2
Order By: Relevance
“…Luoma et al (1983) showed that tolerance to Cu in populations of Macoma balthica and the copepod Acartia clausivaried as much as 10-fold over short distances. Rygg (1985) suggested that a Cu concentration of 200 pg g -' represented a threshold concentration for polychaete communities.…”
Section: Discussionmentioning
confidence: 99%
“…Luoma et al (1983) showed that tolerance to Cu in populations of Macoma balthica and the copepod Acartia clausivaried as much as 10-fold over short distances. Rygg (1985) suggested that a Cu concentration of 200 pg g -' represented a threshold concentration for polychaete communities.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of copper in sediments have been inferred to be causally related to the species composition of infauna in Norwegian fjords (Rygg 1985a). Effects on infaunal species con~position were detected at sediment concentrations ranging from 5 to 10 times above presumed background concentrations.…”
Section: Introductionmentioning
confidence: 96%
“…However, excessive amounts of heavy metals enter the coastal environment via anthropogenic industrial activities, mining activities, agriculture (run-off), and sewage disposal [33,34], are considered toxic and restrain the growth and propagation of macrobenthic organisms [35][36][37]. Rygg has found negative correlations between species diversity in macrobenthic community and copper concentrations and organic matter [38]. McLusky et al [39] also showed that higher concentrations of Cu were toxic to macrobenthos and lowered their diversity.…”
Section: Influence Of Physical and Chemical Characteristics Of Sedimentsmentioning
confidence: 99%